Outer measures and associated lattice properties - Peter M. Grassi (International Journal of Mathematics and Mathematical Sciences)
Zero-one measure characterizations of lattice properties such as normality are extended to more general measures. For a given measure, we consider two associated outer measures and attempt to obtain the outer-measurable sets. We also seek necessary and sufficient conditions for the measure and outer measures to be equal on the lattice or its complement.